FAKTOR PENGARUH RENTABILITAS EKONOMI PADA KOPERASI SIMPAN PINJAM PENGEMBANGAN PEDESAAN (KSP3) CABANG LAHUSA - Nofridawati Hulu (Universitas Nias Raya, 2023)
The research aims to describe the factors influencing economic profitability, cooperative profitability strategies. The approach and type of research used is qualitative with a qualitative descriptive approach. Employee research data sources (KSP3). Data obtained from the results of interviews and documentation observations, with qualitative descriptive analysis techniques. The results of the study are 1) The factors that influence economic profitability in cooperatives are bad loans, late repayment of loan installments to cooperatives, and the occurrence of the Covid-19 Pendemic. 2) the cooperative’s profitability strategy is to open a schedule for accepting new members, providing loan installments. Conclusion 1) the factors that influence profitability are the length of loan installments, the occurrence of bad loans and the Covid-19 Pendemic. 2) cooperative profitability strategy is to accept new members, and want to provide loans under shares and above shares. The research suggests 1) the cooperativen should be able to provide low loan interest rates and be able to borrow members to return the interest in percent at maturity.